(untitled) (Proceedings of the International Conference of Community Health and Medical Sciences, 2024)
Chronic wounds are defined as acute wounds that fail to heal within the expected time. The proliferative phase is one of four major phases in healing physiology that occurs on days 8 to 11, characterized by epithelial cell contraction leading to the edges merging and the wound size decreased. New treatments for chronic wounds have been developed, including medical plasma. Plasma is an ionized gas. Plasma generates RONS molecules, which can be effective in healing chronic wounds but histological view has not been reported. The aim of this study was to calculate the number of inflammatory cells, blood vessels, fibroblasts, the percentage of re-epithelialization, and the thickness of necrosis of chronic wound tissue in mice skin treated with plasma in the proliferation phase. The sample used tissue slides of mice skin with chronic wounds on the 11th day which had been treated with plasma daily. A total of 18 samples were divided into 4 groups. Control (K) chronic wound tissue without treatment, Contact Plasma (CP) chronic wound tissue with 5mm distance of plasma treatment, Contact-Noncontact Plasma (CP-NCP) chronic wound tissue with combination plasma treatment, days 0-6 distance of 5 mm and days 7-13 distance of 20 mm, Non-contact Plasma (NCP) chronic wound tissue with 20mm distance of plasma treatment. The results showed that the highest mean number of fibroblast cells, blood vessels, and percentage re-epithelialization were found in CP-NCP. The highest number of inflammatory cells was in K and the highest thickness of necrosis 70.5µm was found in CP. The final conclusion, the highest average number of fibroblast cells, blood vessels, and percentage of re-epithelialization was found in CP-NCP group indicated the CP-NCP group had the fastest healing process compared to the others. Thus, contact-non-contact plasma medical treatment has potential as a new treatment for chronic wounds.